Hubungan Asupan Energy Dengan Status Gizi Anak Pra Sekolah Usia 4-5 Tahun Di TK Al Islam Jamsaren Surakarta - Anik Kurniawati; Endang Suwanti (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: The nutritional status of children is influenced by two factors, namely the direct factor in food intake and infectious diseases and indirect causes. Nutritional factors are known to play an important role in determining the growth of a child. When experiencing growth, cells in the body need energy to divide, if energy requirements are not met, cell division will be inhibited and the effect will be seen through anthropometric and biochemical parameters. Objective, To determine the relationship between energy intake and nutritional status of preschoolers aged 4-5 years at Al Islam 1 Jamsaren Kindergarten in Surakarta. The research hypothesis, there is a relationship between energy intake and nutritional status of pre-school age children 4-5 years old at Al Islam Jamsaren Kindergarten in Surakarta. Method: This type of research is this study using a cross sectional approach. The target population in this study was the population in this study were all mothers and children aged 4-5 years in Al Islam 1 TK Jamsaren Surakarta totaling 89 people. Samples were taken by purposive technique with a sample of 47 respondents. Analysis of sperman rank test data. Results: Showed that the majority of respondents had a moderate energy intake of 17 (36.2%) respondents and most had good nutritional status 38 (80.8%) respondents. Conclusion: There is a relationship between energy intake and the nutritional status of pre-school children aged 4-5 years in Surakarta Jamsaren Kindergarten with p value 0.02.